Financial procedures and problems in the Ministry of Health / Jamaliah Mokri - Mokri, Jamaliah (1987)
The objective of the function 'Health Service' as the total responsibility of the Ministry Of Health is to raise the health status of Malaysian by providing promotive, preventive, curative and rehabilitative health services with special emphasis to the disadvantage groups, in order that the health of the nation can measure up to the needs of the country's economic development and continuing social progress. For the attainment of this objective due regard will be given to the promotive of national unity.